Organic carbon, age, lithology, and CPI-alkenes at DSDP Sites 57-440 and 56-436 - Simon C Brassell; P A Comet; Geoffrey Eglinton; P J Isaacson; James McEvoy; James R Maxwell; I D Thomson; P J C Tibbetts; John K Volkman (PANGAEA, 1980)
"Bound" and "free" solvent-extractable lipids have been examined from Sections 440A-7-6, 440B-3-5, 440B-8-4, 440B-68-2, and 436-11-4. The compound classes studied include aliphatic and aromatic hydrocarbons, ketones, alcohols, and carboxylic acids. Carotenoids and humic acids have also been examined. The quantitative results are considered in terms of input indicators, diagenesis parameters, and structural classes. A difference in input is deduced across the Japan Trench, with a higher proportion of autochthonous components on the western inner trench slope compared with the more easterly, outer trench, wall and greater input in the early Pleistocene than in the Miocene. A variety of diagenetic transformations is observed at Site 440 as sample depth increases. Results are compared with those of samples from Atlantic Cretaceous sediments and from the Walvis Bay high productivity area.
Supplement to: Brassell, SC et al. (1980): Preliminary lipid analyses of Sections 440A-7-6, 440B-3-5, 440B-8-4, 440B-68-2, and 436-11-4: Legs 56 and 57, Deep Sea Drilling Project. In: Scientific Party, Initial Reports of the Deep Sea Drilling Project, 56/57 (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 56-57, 1367-1390, https://doi.org/10.2973/dsdp.proc.5657.170.1980